2008
DOI: 10.1007/s00068-008-8025-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Routine Spiral CT-Chest Justified in Evaluation of the Major Blunt Trauma Patients?

Abstract: Although the incidence of significant injuries identified by the chest CT scan was low, it did prompt immediate intervention in a significant number of patients; some of them had potentially life-threatening injuries. Routine use of CT scanning is warranted in early evaluation of polytrauma patients or patients with severe blunt chest trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…This rate was significantly less than the results in the other age-dependent groups (74.7-77.8%). However, CT imaging has become essential in the imaging evaluation of trauma patients and is being used with progressively increasing frequency [27,28], caused by the well documented benefit for the outcome of trauma patients [9,29,30]. Nevertheless, a byproduct of the increased use of CT has been the more frequent exposure of injured children to potentially harmful ionizing radiation [27].…”
Section: Discussionmentioning
confidence: 99%
“…This rate was significantly less than the results in the other age-dependent groups (74.7-77.8%). However, CT imaging has become essential in the imaging evaluation of trauma patients and is being used with progressively increasing frequency [27,28], caused by the well documented benefit for the outcome of trauma patients [9,29,30]. Nevertheless, a byproduct of the increased use of CT has been the more frequent exposure of injured children to potentially harmful ionizing radiation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Most missed injuries were lung contusions (n = 94), pneumothoraces (n = 85) and thoracic cage fractures, and in addition, potentially life threatening injuries such as aortic injuries (n = 2) were found ( 8 ). Another study on 443 patients with blunt chest trauma who underwent chest CT revealed 81% additional diagnoses on chest CT in those with an initially normal chest X-ray ( 9 ). Barrios et al showed similar results in retrospective analysis of 200 patients with blunt trauma; chest CT resulted in the diagnosis of 25% more injuries and 6% change in management ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…These patients usually suffered from delayed haemothorax and injuries predominating in the group of blunt injuries. Persistent bleeding to the pleural cavity occurred 2-3 days after trauma, often coexisting with rib polyfractures and usually the result of intercostal artery damage [15,17].…”
Section: Discussionmentioning
confidence: 99%